المواريث والاحتفال بذكرى وفاة الميت في ولاية مينانج كاباو بإندونيسيا بين العادات والفقه الإسلامي: دراسة تقويمية - شمسيور، جيمي هينديكو (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This research focuses on the issue of inheritance and traditional ceremony in commemoration of death in the state of Minangkabau based on state's customs and Islamic jurisprudence. The main objective of this research is to explain the concept of inheritance and its rules, and also the rule of the commemoration of death from the perspective of Islam, to clarify customs and laws on inheritance and traditional ceremony of commemoration of death in the state and what Islamic law says about each, including the views of scholars on the issue. Besides that, it also identifies methods to correct the rules of inheritance and commemoration of death based on the customs, to correct understanding of society about them and to explain the most important differences between customs and Islamic perspective. The research used the inductive approach by collecting of information from sources related to this study, both past and present. It also used the descriptive approach to identify the norms followed by members of the Minangkabau society in the application of the inheritance and commemoration of death, through a direct description of the reality of applications experienced by the society. This research also used the analytical method to analyse and study information contained on this issue. Among the most important findings of this study is that inheritance in Minangkabau can be divided into two parts. First is individual property which applies Islamic rule called al-faraid, and second is ancestors' property or clan's property which they apply custom rules of inheritance. The traditional ceremony to commemorate death currently has irregularities, among them is that the custom necessitate the people to do the commomeration, have a banquet, and slaughter animal during the period, and money is usually taken from property of the dead person. All of these are not permissible under Islamic perspective.